Positive electrode active material, method for producing positive electrode active material, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device
Patent Information
- Application Number
- JP2024543038
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-07-15
Smart Images

Figure 0007634789000019 
Figure 0007634789000020 
Figure 0007634789000021
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of secondary batteries, in particular to a positive electrode active material, a method for producing a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. As secondary batteries have made great strides in development, their energy density, cycle performance and safety performance are also required to be higher. As a conventional positive electrode active material of secondary batteries, lithium manganese phosphate is prone to Li / Mn antisite defects during charging and discharging, and manganese leaching is relatively serious, which affects the gram capacity of secondary batteries and causes the safety performance and cycle performance of secondary batteries to be poor. Summary of the Invention
[0003] The present application has been made in view of the above-mentioned problems, and aims to provide a positive electrode active material, a method for producing a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, which solve the problems of low cycle capacity retention rate, short cycle life, and low safety of secondary batteries produced using conventional positive electrode active materials.
[0004] In order to achieve the above object, a first aspect of the present application provides a positive electrode active material. The positive electrode active material includes a first positive electrode active material and a second positive electrode active material, wherein: The first positive electrode active material is the compound LiNi b Co d Mn e M' fO2, where b is selected from the range of 0.314 to 0.970, d is selected from the range of 0 to 0.320, and optionally from the range of 0.047 to 0.320, and e is selected from the range of 0.006 to 0.390, and the sum of b, d, e and f is 1, and f is greater than 0. M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, and optionally M' is Mg and / or Al. The second positive electrode active material includes a core, a first coating layer that coats the core, and a second coating layer that coats the first coating layer. Here, the core is a compound Li 1+x Mn 1-y A y P 1-z R z O4, and the first coating layer comprises pyrophosphate M a P2O7 and Phosphate X n PO4, and the second coating layer includes carbon. Here, x is selected from the range of -0.100 to 0.100, y is selected from the range of 0.001 to 0.909, and optionally from the range of 0.001 to 0.500, and z is selected from the range of 0.001 to 0.100. a is greater than 0 and equal to or less than 4, and n is greater than 0 and equal to or less than 2. A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally from Zn, Fe, Ti, V, Ni, Co, and Mg. R is one or more elements selected from B, Si, N, and S. M and X are independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Li, Fe and Ag.
[0005] Therefore, the applicant has found that the second positive electrode active material can be obtained by simultaneously doping the Mn site and the P site of the compound LiMnPO4 with a specific amount of a specific element and coating the surface of the compound with two layers, thereby greatly reducing the elution of transition metals and reducing the oxygen activity of the particle surface, promoting the transition of lithium ions, improving the conductive performance and desolvation performance of the material, improving the rate performance of the battery, improving the cycle performance and high temperature performance of the secondary battery, and reducing the corrosion of the active material caused by the electrolyte. The second positive electrode active material only has a one-dimensional lithium ion transmission channel, while the first positive electrode active material is a layered transition metal oxide and has a two-dimensional lithium ion transmission channel. Therefore, the present application uses a mixture of the first positive electrode active material and the second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0006] Unless otherwise noted, the chemical formula is Li 1+x Mn 1-y A y P 1-z R z In O4, when A is two or more elements, the above-mentioned limitation on the numerical range of y is not only a limitation of the stoichiometric number of each type of element that becomes A, but also a limitation of the sum of the stoichiometric numbers of each element that becomes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers y1, y2...yn of A1, A2...An must each be within the numerical range in which y is limited by this application, and the sum of y1, y2...yn must also be within this numerical range. Similarly, when R is two or more elements, the limitation on the numerical range of the stoichiometric numbers of R in this application also has the above meaning. Similarly, a compound having the chemical formula LiNi b Co d Mn e M' f When M' in O2 is two or more elements, the numerical range limitations of the stoichiometric number of M' in this application also have the above meaning.
[0007] In any embodiment, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2% to 55%, and optionally 3% to 50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0008] In any of the embodiments, the value of b×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby making it possible to further improve the stability and safety of the entire positive electrode active material.
[0009] In any of the embodiments, the first positive electrode active material is a single crystal or pseudo-single crystal material, and the particle size D of the first positive electrode active material is v 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0010] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0011] In any embodiment, when the first cathode active material is a single crystal or pseudo single crystal material, d is selected from the range of 0.047 to 0.320, optionally selected from the range of 0.047 to 0.282, and / or b is greater than 0.314 and less than 0.97, and is selectively selected within the range of 0.55 to 0.869.
[0012] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0013] In any embodiment, when the first positive electrode active material is a polycrystalline material, the particle size D of the first positive electrode active material is v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and selectively 1.32m 2 / g or less, and more selectively, 0.28 to 1.32 m 2 / g, and / or The first positive electrode active material has a compacted density of 2.90 g / cm at a pressure of 3 T. 3 or more, and optionally 2.92 g / cm 3 or more, more selectively, 2.92 to 3.31 g / cm 3 It is.
[0014] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0015] In any embodiment, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1.05% or less, optionally 1% or less, and / or the mass content of lithium hydroxide is 1.02% or less, optionally 1% or less.
[0016] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF. HF is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0017] In any one of the embodiments, in the second positive electrode active material, the crystal plane spacing of the pyrophosphate in the first coating layer is 0.293 to 0.326 nm, and the angle of the crystal orientation (111) is 26.41° to 32.57°, and / or The crystal plane spacing of the phosphate in the first coating layer is 0.345 to 0.358 nm, and the angle formed with the (111) crystal orientation is 24.25° to 26.45°.
[0018] When the angle between the crystal plane spacing of the phosphate and pyrophosphate in the first coating layer and the crystal orientation (111) is within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.
[0019] In any embodiment, in the core of the second positive electrode active material, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above condition is satisfied, the energy density and cycle performance of the manufactured secondary battery can be further improved.
[0020] In any embodiment, in the core of the second positive electrode active material, the ratio of z to 1-z is 1:999 to 1:9, and optionally 1:499 to 1:249, where z represents the sum of the stoichiometric numbers of the elements doped in the P site. When the above condition is satisfied, the energy density and cycle performance of the manufactured secondary battery can be further improved.
[0021] In any embodiment, in the second positive electrode active material, the coating amount of the first coating layer is greater than 0 wt % and not more than 7 wt %, and optionally 4 to 5.6 wt %, based on the weight of the core.
[0022] When the coating amount of the first coating layer is within the above range, the leaching of manganese can be further suppressed, the transmission of lithium ions can be further promoted, the impedance of the secondary battery can be further reduced, and the dynamic performance of the secondary battery can be further improved.
[0023] In any embodiment, in the second positive electrode active material, the weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:1, and optionally 1:3 to 1:1.
[0024] By using a suitable compounding ratio of pyrophosphate and phosphate, the synergistic effect of the two can be fully exerted, which is advantageous in reducing the impedance of the secondary battery and further suppressing the elution of manganese.
[0025] In any embodiment, in the second positive electrode active material, the crystallinity of the pyrophosphate and the crystallinity of the phosphate are each independently 10% to 100%, and optionally 50% to 100%.
[0026] In the first coating layer of the lithium manganese phosphate positive active material of the present application, the pyrophosphate and phosphate with a certain degree of crystallinity are advantageous for maintaining the structural stability of the first coating layer and reducing lattice defects. On the one hand, this is advantageous for the pyrophosphate to fully exert the effect of inhibiting the dissolution of manganese, and on the other hand, this is advantageous for the phosphate to reduce the heterolithium content on the surface and the valence of the surface oxygen. This reduces the interfacial side reaction between the positive electrode material and the electrolyte, reduces the consumption of the electrolyte, and improves the cycle performance and safety performance of the secondary battery.
[0027] In any embodiment, in the second positive electrode active material, the coating amount of the second coating layer is greater than 0 wt % and not more than 6 wt %, and optionally 3 to 5 wt %, based on the weight of the core.
[0028] The carbon-containing layer, which is the second coating layer, on the one hand, exerts a "barrier" function and can avoid direct contact between the positive electrode active material and the electrolyte, thereby reducing the corrosion of the positive electrode active material by the electrolyte and improving the safety performance of the battery at high temperatures. On the other hand, it has a relatively strong conductive ability and can reduce the internal resistance of the secondary battery, thereby improving the dynamic performance of the secondary battery. However, since the gram capacity of the carbon material is relatively low, when the amount of the second coating layer used is too large, it may reduce the gram capacity of the entire positive electrode active material. Therefore, when the coating amount of the second coating layer is in the above range, the dynamic performance and safety performance of the secondary battery can be further improved without sacrificing the gram capacity of the positive electrode active material.
[0029] In any embodiment, A is at least two selected from Fe, Ti, V, Ni, Co and Mg.
[0030] In any embodiment, the second positive electrode active material has a Li / Mn antisite defect concentration of 4% or less, and optionally 2% or less. In the second positive electrode active material of the present application, the Li / Mn antisite defect is a LiMnPO4 lattice defect. + and Mn 2+ The position of Li is exchanged. + The transmission channel is a one-dimensional channel, and Mn 2+ Li + The antisite defect Mn 2+ Li + By controlling the Li / Mn antisite defect concentration to a low level, the gram capacity and rate performance of LiMnPO4 can be improved.
[0031] In any embodiment, the lattice change rate of the second positive electrode active material before and after the complete release of lithium is 6% or less, and optionally 4% or less. During the release of lithium from LiMnPO4, it is a two-phase reaction. The interface stress between the two phases is determined by the magnitude of the lattice change rate. The smaller the lattice change rate and the smaller the interface stress, the greater the Li + Therefore, the decrease in the lattice change rate of the core is + This is advantageous in reinforcing the transmission capability of the secondary battery, thereby improving the rate performance of the secondary battery.
[0032] In any of the embodiments, the surface oxygen valence of the second positive electrode active material is -1.88 or less, and selectively -1.98 to -1.88. This is because the higher the valence of the oxygen compound, the stronger its ability to obtain electrons, i.e., its oxidizing property. On the other hand, in the second positive electrode active material of the present application, the surface valence of oxygen is controlled to a relatively low level, thereby reducing the reaction activity of the positive electrode material surface and reducing the interfacial side reaction between the positive electrode material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.
[0033] In any embodiment, the second positive electrode active material has a packed density at 3 T of 2.0 g / cm 3 or more, and optionally 2.2 g / cm 3 The higher the compaction density of the second positive electrode active material, that is, the greater the weight of the active material per unit volume, the more advantageous it is for increasing the volumetric energy density of the secondary battery.
[0034] A second aspect of the present application further provides a method for producing a cathode active material, the method comprising: providing a first active cathode material and a second active cathode material; mixing a first positive electrode active material with a second positive electrode active material; The first positive electrode active material is the compound LiNi b Co d Mn e M' f Contains O2, The second positive electrode active material includes a core, a first coating layer coating the core, and a second coating layer coating the first coating layer. Here, the core is the compound Li 1+x Mn 1-y A y P 1-z R z Contains O4, The first coating layer is pyrophosphate M a P2O7 and Phosphate X n PO4 and The second coating layer includes carbon. wherein the definitions of a, b, d, e, f, x, y, z, n, A, R, M, X and M' are as described in the first aspect of the present application. Optionally, the first positive electrode active material further includes lithium carbonate and / or lithium hydroxide.
[0035] In this way, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0036] A third aspect of the present application provides a positive electrode plate. The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. The positive electrode film layer includes the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application, and optionally, the content of the positive electrode active material in the positive electrode film layer is 10 wt% or more, and further optionally, 95 to 99.5 wt%, based on the total weight of the positive electrode film layer.
[0037] A fourth aspect of the present application provides a secondary battery comprising the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0038] A fifth aspect of the present application provides a battery module, the battery module including the secondary battery of the fourth aspect of the present application.
[0039] A sixth aspect of the present application provides a battery pack, the battery pack including the battery module of the fifth aspect of the present application.
[0040] A seventh aspect of the present application provides a power consumption device, the power consumption device including at least one selected from the secondary battery of the fourth aspect of the present application, the battery module of the fifth aspect of the present application, and the battery pack of the sixth aspect of the present application. [Brief description of the drawings]
[0041] [Figure 1] FIG. 2 is a schematic diagram of a second positive electrode active material having a core-shell structure according to an embodiment of the present application. [Diagram 2] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 3] FIG. 3 is an exploded view of the secondary battery shown in FIG. 2 according to an embodiment of the present application. [Figure 4] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Diagram 5] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of the battery pack shown in FIG. 5 according to an embodiment of the present application. [Figure 7] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] Hereinafter, with reference to the drawings as appropriate, embodiments specifically disclosing the positive electrode active material, the method for manufacturing the positive electrode active material, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and do not limit the subject matter described in the claims.
[0043] The "ranges" disclosed in this application are defined in the form of lower and upper limits. A given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such a defined range may or may not include the end values, and any combination is possible. That is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. It is noted that if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, a numerical range "a-b" represents a shorthand representation of any combination of real numbers a-b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is only a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that this parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, a method including steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, a method described may further include step (c) means that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0047] Unless otherwise stated, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0048] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).
[0049] Unless otherwise specified, in this application, the median particle size Dv 50is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%. In this application, the median particle size Dv 50 can be measured using laser diffraction particle size analysis, for example see standard GB / T 19077-2016, using a laser particle size analyzer (e.g. Malvern Master Size 3000).
[0050] Unless otherwise specified, in this application, the term "coating layer" refers to a material layer coated on a core, and the material layer may completely or partially cover the core. The term "coating layer" is used merely for ease of description and is not intended to limit the present invention. Similarly, the term "thickness of the coating layer" refers to the thickness of the material layer coated on the core in the radial direction of the core.
[0051] Unless otherwise specified, in this application, a "source" refers to a compound that is a source of a certain element, and illustrative types of "source" include, but are not limited to, carbonates, sulfates, nitrates, elements, halides, oxides, and hydroxides.
[0052] [Secondary battery] A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be continuously used by activating the active material through charging after the battery is discharged.
[0053] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During charging and discharging of the battery, active ions (e.g., lithium ions) shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short circuiting between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive electrode plate and the negative electrode plate.
[0054] [Cathode active material] One embodiment of the present application provides a positive electrode active material. The positive electrode active material includes a first positive electrode active material and a second positive electrode active material, wherein: The first positive electrode active material is the compound LiNi b Co d Mn e M' f O2. Here, b is selected from the range of 0.314 to 0.970, and optionally from the range of 0.340 to 0.970. d is selected from the range of 0 to 0.320, and optionally from the range of 0.005 to 0.320, and further optionally from the range of 0.047 to 0.320. e is selected from the range of 0.006 to 0.390, and optionally from the range of 0.006 to 0.280. The sum of b, d, e and f is 1, and f is greater than 0. M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, and optionally M' is Mg and / or Al. The second positive electrode active material includes a core, a first coating layer that coats the core, and a second coating layer that coats the first coating layer. Here, the core is a compound Li 1+x Mn 1-y A y P 1-z R z The first coating layer contains pyrophosphate M a P2O7 and Phosphate X nPO4, and the second coating layer includes carbon, where x is selected from the range of -0.100 to 0.100, y is selected from the range of 0.001 to 0.909, optionally selected from the range of 0.091 to 0.909, or optionally selected from the range of 0.001 to 0.500, z is selected from the range of 0.001 to 0.100, a is greater than 0 and less than or equal to 4, optionally 3 or 4, n is greater than 0 and less than or equal to 2, optionally 2, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, optionally one or more elements selected from Zn, Fe, Ti, V, Ni, Co, and Mg, and further optionally one or more elements selected from Fe, V, Co, and Mg. R is one or more elements selected from B, Si, N and S, and optionally one or more elements selected from Si, N and S. M and X are independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Li, Fe and Ag.
[0055] The first positive electrode active material is a layered transition metal oxide and has a two-dimensional lithium ion transmission channel. The second positive electrode active material only has a one-dimensional lithium ion transmission channel. By using the two in combination, the advantages can be complemented and the overall electrochemical performance can be improved. The initial clone efficiency of the first positive electrode active material is generally lower than that of the second positive electrode active material. By using the two in combination, the secondary battery contains a large amount of reversible lithium ions even after the chemical negative electrode film formation is consumed, improving the cycle capacity retention rate of the secondary battery, extending the cycle life of the secondary battery, and improving the safety of the secondary battery.
[0056] In addition, although the mechanism is not yet clear, the applicant has discovered that the second positive electrode active material of the present application has a core-shell structure having two coating layers, in which the core is Li 1+x Mn 1-y A y P 1-z Rz It was found that the core contains O4. The element A doped into the manganese site of the lithium manganese phosphate reduces the lattice change rate of the lithium manganese phosphate during lithium release, improves the structural stability of the lithium manganese phosphate positive electrode material, and contributes to significantly reducing the dissolution of manganese and reducing the oxygen activity of the particle surface. The element R doped into the phosphorus site contributes to changing the difficulty of the change in Mn-O bond length, thereby reducing the transition barrier of lithium ions, promoting the transition of lithium ions, and improving the rate performance of the secondary battery. The first coating layer of the second positive electrode active material of the present application includes pyrophosphate and phosphate. Since the transition barrier in the pyrophosphate of the transition metal is relatively high (>1 eV), the dissolution of the transition metal can be effectively suppressed. Meanwhile, the phosphate has excellent lithium ion conducting ability and can reduce the heterolithium content of the surface. In addition, since the second coating layer is a carbon-containing layer, the conductive performance and desolvation ability of LiMnPO4 can be effectively improved. In addition, the "barrier" effect of the second coating layer can further inhibit the transition of manganese ions to the electrolyte and reduce the corrosion of the positive electrode active material by the electrolyte. Therefore, the second positive electrode active material of the present application can effectively suppress the dissolution of Mn during lithium release and promote the transition of lithium ions by doping lithium manganese phosphate with a specific element and surface coating it. This improves the rate performance of the cell and improves the cycle performance and high temperature performance of the secondary battery. In addition, the fact that the position of the main characteristic peak of the second positive electrode active material of the present application is almost the same as that before doping with LiMnPO4 indicates that there is no impurity phase in the doped lithium manganese phosphate positive electrode active material, and the improvement of the secondary battery performance is mainly due to element doping, not due to the impurity phase.
[0057] In some embodiments, M' is Mg and / or Al. Doping the first positive electrode active material with Al element can increase the structural and thermal stability of the material and improve the cycling performance. Doping the first positive electrode active material with Mg element increases or decreases the transition metal ion valence. This generates holes or electrons, which can change the band structure of the material, improve the intrinsic electronic conductivity of the material, and improve the cycling performance of the secondary battery. Co-doping Mg and Al into the lattice of the main body material can synergistically stabilize the material structure, improve the miscibility of the material cations, suppress oxygen precipitation, and further improve the cycling performance and thermal stability of the secondary battery.
[0058] Unless otherwise noted, the chemical formula is Li 1+x Mn 1-y A y P 1-z R z In O4, when A is two or more elements, the above-mentioned limitation on the numerical range of y is not only a limitation of the stoichiometric number of each type of element that becomes A, but also a limitation of the sum of the stoichiometric numbers of each element that becomes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers y1, y2...yn of A1, A2...An must each be within the numerical range in which y is limited by this application, and the sum of y1, y2...yn must also be within this numerical range. Similarly, when R is two or more elements, the limitation on the numerical range of the stoichiometric numbers of R in this application also has the above meaning. Similarly, a compound having the chemical formula LiNi b Co d Mn e M' f When M' in O2 is two or more elements, the numerical range limitations of the M' stoichiometric number in this application also have the above meanings.
[0059] As shown in FIG. 1, the second positive electrode active material having a core-shell structure of the present application includes a core 11, a first coating layer 12 that coats the core 11, and a second coating layer 13 that coats the first coating layer 12. Here, the core 11 is Li 1+x Mn 1-y A y P1-z R z O4. Core 11 contributes to reducing the lattice change rate of lithium manganese phosphate during lithium release of element A doped into the manganese site of lithium manganese phosphate, improving the structural stability of lithium manganese phosphate positive electrode material, greatly reducing the dissolution of manganese and reducing the oxygen activity on the particle surface. Element R doped into the phosphorus site contributes to changing the difficulty of the change in Mn-O bond length, thereby reducing the transition barrier of lithium ions, promoting the transition of lithium ions, and improving the rate performance of secondary batteries.
[0060] In some embodiments, the compound LiNi b Co d Mn e M' f O2 and Li 1+x Mn 1-y A y P 1-z R z All O4's maintain electroneutrality.
[0061] In some embodiments, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2%-55%, optionally 3%-50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0062] In some embodiments, the value of b×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby further improving the stability and safety of the entire positive electrode active material.
[0063] In some embodiments, the first active cathode material is a single crystal or pseudo-single crystal material, and the particle size D of the first active cathode material is v 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0064] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0065] In some embodiments, when the first active cathode material is a single crystal or pseudo single crystal material, d is selected from the range of 0.047 to 0.320, optionally selected from the range of 0.047 to 0.282, and / or b is greater than 0.314 and less than 0.97, optionally selected from the range of 0.55 to 0.869.
[0066] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0067] In some embodiments, when the first active cathode material is a polycrystalline material, the particle size D of the first active cathode material is v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and selectively 1.32m 2 / g or less, and more selectively, 0.28 to 1.32 m 2 / g, and / or The first positive electrode active material has a compacted density of 2.90 g / cm at a pressure of 3 T. 3 or more, and optionally 2.92 g / cm 3 or more, more selectively, 2.92 to 3.31 g / cm 3 It is.
[0068] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0069] In some embodiments, the first active cathode material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1.05% or less, optionally 1% or less, and / or the mass content of lithium hydroxide is 1.02% or less, optionally 1% or less.
[0070] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF, which is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0071] In some embodiments, in the second positive electrode active material, the crystal plane spacing of the pyrophosphate in the first coating layer is 0.293 to 0.326 nm, and the angle of the crystal orientation (111) is 26.41° to 32.57°; and / or The crystal plane spacing of the phosphate in the first coating layer is 0.345 to 0.358 nm, and the angle formed with the (111) crystal orientation is 24.25° to 26.45°.
[0072] When the angle between the crystal plane spacing of the phosphate and pyrophosphate in the first coating layer and the crystal orientation (111) is within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.
[0073] In some embodiments, in the core of the second positive electrode active material, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above condition is met, the energy density and cycle performance of the manufactured secondary battery can be further improved.
[0074] In some embodiments, in the core of the second positive electrode active material, the ratio of z to 1-z is 1:999 to 1:9, and optionally 1:499 to 1:249, where z represents the sum of the stoichiometric numbers of the elements doped in the P site. When the above condition is met, the energy density and cycle performance of the fabricated secondary battery can be further improved.
[0075] In some embodiments, in the second positive electrode active material, the coating amount of the first coating layer is greater than 0 wt % and 7 wt % or less, and optionally 4 to 5.6 wt %, based on the weight of the core.
[0076] When the coating amount of the first coating layer is within the above range, the leaching of manganese can be further suppressed, the transmission of lithium ions can be further promoted, the impedance of the secondary battery can be further reduced, and the dynamic performance of the secondary battery can be further improved.
[0077] In some embodiments, in the second positive electrode active material, the weight ratio of pyrophosphate to phosphate in the first coating layer is from 1:3 to 3:1, and optionally from 1:3 to 1:1.
[0078] By using a suitable compounding ratio of pyrophosphate and phosphate, the synergistic effect of the two can be fully exerted, which is advantageous in reducing the impedance of the secondary battery and further suppressing the elution of manganese.
[0079] In some embodiments, in the second positive electrode active material, the crystallinity of the pyrophosphate and the crystallinity of the phosphate are each independently between 10% and 100%, and optionally between 50% and 100%.
[0080] In the first coating layer of the lithium manganese phosphate positive active material of the present application, the pyrophosphate and phosphate with a certain degree of crystallinity are advantageous for maintaining the structural stability of the first coating layer and reducing lattice defects. On the one hand, this is advantageous for the pyrophosphate to fully exert the effect of inhibiting the dissolution of manganese, and on the other hand, this is advantageous for the phosphate to reduce the heterolithium content on the surface and the valence of the surface oxygen. This reduces the interfacial side reaction between the positive electrode material and the electrolyte, reduces the consumption of the electrolyte, and improves the cycle performance and safety performance of the secondary battery.
[0081] In some embodiments, in the second positive electrode active material, the coating amount of the second coating layer is greater than 0 wt % and not more than 6 wt %, and optionally 3 to 5 wt %, based on the weight of the core.
[0082] The carbon-containing layer, which is the second coating layer, on the one hand, exerts a "barrier" function and can avoid direct contact between the positive electrode active material and the electrolyte, thereby reducing the corrosion of the active material by the electrolyte and improving the safety performance of the battery at high temperatures. On the other hand, it has a relatively strong conductive ability and can reduce the internal resistance of the battery, thereby improving the dynamic performance of the secondary battery. However, since the gram capacity of the carbon material is relatively low, when the amount of the second coating layer used is too large, it may reduce the gram capacity of the entire positive electrode active material. Therefore, when the coating amount of the second coating layer is in the above range, the dynamic performance and safety performance of the secondary battery can be further improved without sacrificing the gram capacity of the positive electrode active material.
[0083] In some embodiments, A is at least two elements selected from Fe, Ti, V, Ni, Co and Mg.
[0084] In some embodiments, the second active cathode material has a Li / Mn antisite defect concentration of 4% or less, and optionally 2% or less. In the second active cathode material of the present application, the Li / Mn antisite defect is a LiMnPO4 lattice defect that is formed by dissociating Li + and Mn 2+ The position of Li is exchanged. + The transmission channel is a one-dimensional channel, and Mn 2+ Li + The antisite defect Mn 2+ Li + By controlling the Li / Mn antisite defect concentration to a low level, the gram capacity and rate performance of LiMnPO4 can be improved.
[0085] In some embodiments, the lattice change rate of the second positive electrode active material before and after complete lithium release is 6% or less, and optionally 4% or less. During lithium release from LiMnPO4, it is a two-phase reaction. The interface stress between the two phases is determined by the magnitude of the lattice change rate. The smaller the lattice change rate and the smaller the interface stress, the more the Li + Therefore, the decrease in the lattice change rate of the core is + This is advantageous in reinforcing the transmission capability of the secondary battery, thereby improving the rate performance of the secondary battery.
[0086] In some embodiments, the surface oxygen valence of the second positive electrode active material is -1.88 or less, and selectively -1.98 to -1.88. This is because the higher the valence of the oxygen compound, the stronger its ability to obtain electrons, i.e., its oxidizing property. On the other hand, in the second positive electrode active material of the present application, the surface valence of oxygen is controlled to a relatively low level, thereby reducing the reaction activity of the positive electrode material surface and reducing the interfacial side reaction between the positive electrode material and the electrolyte. This improves the cycle performance and high-temperature storage performance of the secondary battery.
[0087] In some embodiments, the second positive electrode active material has a packed density at 3 T of 2.0 g / cm 3 or more, and optionally 2.2 g / cm3 The higher the compaction density of the second positive electrode active material, that is, the greater the weight of the active material per unit volume, the more advantageous it is for increasing the volumetric energy density of the secondary battery.
[0088] In some embodiments, x is selected from the range of −0.001 to 0.001, y is selected from the range of 0.400 to 0.909, and z is selected from the range of 0.001 to 0.005. a is 3 or 4, and n is 2.
[0089] In some embodiments, b may be, for example, 0.4, 0.5, 0.6, 0.65, 0.7, 0.8, or 0.9.
[0090] In some embodiments, d may be, for example, 0.05, 0.1, 0.15, 0.188, 0.2, 0.25, or 0.3.
[0091] In some embodiments, e may be, for example, 0.01, 0.02, 0.05, 0.1, 0.102, 0.15, 0.2, 0.26, 0.3, or 0.35.
[0092] In some embodiments, x may be, for example, −0.05, −0.03, −0.01, 0, 0.01, 0.02, 0.06, 0.08, or 0.09.
[0093] In some embodiments, y may be, for example, 0.001, 0.002, 0.003, 0.004, 0.1, 0.2, 0.3, 0.4, or 0.5.
[0094] In some embodiments, z may be, for example, 0.001, 0.002, 0.003, 0.004, 0.006, 0.01, 0.02, 0.05, 0.07, 0.08, or 0.09.
[0095] In some embodiments, a can be 1, 2, 3, or 4, for example.
[0096] In some embodiments, n may be 1 or 2, for example.
[0097] [Method for producing positive electrode active material] One embodiment of the present application provides a method for producing a cathode active material, the method comprising the steps of: providing a first active cathode material and a second active cathode material; and mixing the first positive electrode active material with the second positive electrode active material. The first positive electrode active material is the compound LiNi b Co d Mn e M' f Contains O2, The second positive electrode active material includes a core, a first coating layer coating the core, and a second coating layer coating the first coating layer. Here, the core is the compound Li 1+x Mn 1-y A y P 1-z R z O4, and the first coating layer comprises pyrophosphate M a P2O7 and Phosphate X n PO4, and the second coating layer comprises carbon, wherein a, b, d, e, f, x, y, z, n, A, R, M, X, and M' are defined as described in "[Positive Electrode Active Material]", Optionally, the first positive electrode active material further includes lithium carbonate and / or lithium hydroxide.
[0098] As a result, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the electrochemical performance of the secondary battery, improve the cycle capacity retention rate of the secondary battery, and extend the cycle life of the secondary battery.
[0099] In some embodiments, the first active cathode material is prepared by the following steps. Step 1): reacting Ni salt, Co salt, Mn salt with an alkali in a solvent, and then performing solid-liquid separation to collect a solid phase; Step 2): Mixing the solid phase material, the lithium source, and the source of element M, ball milling, sintering, and cooling to obtain a first positive electrode active material; Optionally, in step 2), the first positive electrode active material after cooling is crushed and sieved, or the first positive electrode active material after cooling is crushed, resintered, crushed, and sieved.
[0100] In some embodiments, in step 1), the reaction is carried out under conditions of a pH value of 9-13, and optionally under conditions of a pH value of 9-12 or 10-13.
[0101] In some embodiments, in step 1), the reaction temperature is between 40°C and 80°C, for example 50°C, 55°C, 60°C.
[0102] In some embodiments, in step 1), the reaction time is 8 to 70 hours, for example, 20 hours, 55 hours, 60 hours, 65 hours.
[0103] In some embodiments, in step 1), the reaction is carried out under conditions of a rotation speed of 150 to 1000 r / min, for example, 300 r / min or 500 r / min.
[0104] In some embodiments, in step 1), the solid-liquid separation is performed by filtration.
[0105] In some embodiments, prior to step 2), the solid phase is washed, dried, and optionally vacuum dried at 100° C.-140° C. for 12-48 h, such as at 120° C. for 24 h.
[0106] In some embodiments, in step 2), the rotation speed of the ball mill is 200-500 r / s, for example, 300 r / s, 500 r / s.
[0107] In some embodiments, in step 2), the ball milling time is 1-5 h, for example, 2, 3, 4 h.
[0108] In some embodiments, in step 2), sintering is performed in an air atmosphere, optionally at 0.1-0.4 MPa.
[0109] In some embodiments, in step 2), the sintering procedure is to increase the temperature to 750°C-950°C and hold for 12-20 hours for pre-sintering, with a heating rate of 1°C / min. Optionally, decrease the temperature to 600°C at the same rate and hold for 8 hours for sintering, and after sintering, decrease the temperature to 300°C at a rate of 1°C / min.
[0110] In some embodiments, in step 2), the re-sintering procedure is to heat the material to 400°C at a rate of 20°C / min, hold the material at this temperature for 20 hours, and then cool the material to 300°C at a rate of 1°C / min after sintering.
[0111] In some embodiments, in step 2), the pulverization is performed using an airflow pulverizer. Optionally, the rotation speed of the airflow pulverizer is 2500-3500 r / min, for example 3000 r / min. Optionally, the airflow of the airflow pulverizer is 400-600 m 3 / h, e.g. 500m 3 / h.
[0112] In some embodiments, step 2) involves sieving through a 450-550 mesh (eg, 500 mesh) screen.
[0113] In some embodiments, the second method of making an active cathode material includes the following steps. Providing a core material: The core material is Li 1+x Mn 1-y A y P 1-z R zO4. Here, x is any number within the range of -0.100 to 0.100, y is any number within the range of 0.001 to 0.500, and z is any number within the range of 0.001 to 0.100. A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and is optionally one or more selected from Zn, Fe, Ti, V, Ni, Co, and Mg. R includes one or more elements selected from B, Si, N, and S. Coating step: Pyrophosphate M a Powder containing P2O7, carbon source and phosphate X n PO4. A suspension comprising a core material and pyrophosphate M a Powder containing P2O7, carbon source and phosphate X n PO4 and a suspension containing the same, followed by sintering to obtain a positive electrode active material, wherein M and X are independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li, Fe, and Ag; Here, the second positive electrode active material has a core-shell structure and includes a core and a shell that covers the core. The core is Li 1+x Mn 1-y A y P 1-z R z O4. The shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer. The first coating layer is made of pyrophosphate M a P2O7 and Phosphate X n PO4, and the second coating layer includes elemental carbon.
[0114] In some embodiments, the step of providing the core material comprises the steps of: Step (1): mixing a manganese source, a source of element A, and an acid to obtain a mixture; Step (2): Mix the mixture with a lithium source, a phosphorus source, a source of element R, and a selective solvent, and sinter under the protection of an inert gas to obtain Li 1+x Mn 1-yA y P 1-z R z Obtaining a core material containing O4, where A and R are as defined above.
[0115] In some embodiments, step (1) is carried out at 20°C to 120°C, optionally at 40°C to 120°C (e.g., about 30°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C or about 120°C), and / or, in step (1), the mixture is stirred at a rotation speed of 400 to 700 rpm for 1 to 9 hours (alternatively, for example, 3 to 7 hours, e.g., about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours or about 9 hours).
[0116] In some embodiments, in step (2), the mixture is mixed at a temperature of 20-120° C., optionally 40-120° C. (e.g., about 30° C., about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.) for 1-10 hours (e.g., about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 11 hours, or about 12 hours).
[0117] In some embodiments, in step (2), the mixing is performed under a condition of a pH of 3.5 to 6, optionally the pH is 4 to 6, and further optionally the pH is 4 to 5. In the present application, the pH may be adjusted by a method commonly used in the art, for example, by adding an acid or an alkali.
[0118] In some embodiments, optionally in step (2), the molar ratio of the mixture or the manganese salt particles doped with element A, the lithium source, and the phosphorus source is 1:0.5-2.1:0.5-2.1, optionally about 1:1:1.
[0119] In some embodiments, in step (2), sintering is performed at 600 to 950°C for 4 to 10 hours in an atmosphere of inert gas or a mixture of inert gas and hydrogen gas. Optionally, the protective atmosphere is a mixture of 70 to 90% by volume of nitrogen gas and 10 to 30% by volume of hydrogen gas. Optionally, sintering may be performed at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Optionally, the sintering temperature and sintering time may be within any range of any of the above values. This improves the crystallinity of the core, reduces the generation of heterophase, and maintains the core at a constant particle size. As a result, the gram capacity and compaction density of the positive electrode active material are improved, and the overall performance of the secondary battery, including the rate performance, is improved.
[0120] In some optional embodiments, the mixture obtained in step (1) is filtered, dried, and ground to obtain manganese salt particles doped with element A and having a particle size Dv50 of 50-200 nm. The manganese salt particles doped with element A are used to mix with a lithium source, a phosphorus source, a source of element R, and an optional solvent in step (2).
[0121] In some optional embodiments, the mixture after mixing in step (2) is dried to obtain a powder material, and the powder material is sintered to obtain Li. 1+x Mn 1-y A y P 1-z R z Obtain core material containing O4.
[0122] In some embodiments, a powder containing pyrophosphate MP2O7 is produced by the following steps: A source of element M, a phosphorus source and an optional solvent are mixed to obtain a mixture, the pH of the mixture is adjusted to 4-6, and the mixture is kept mixed, dried and sintered.
[0123] In some embodiments, in the step of preparing the powder comprising pyrophosphate MP2O7, the drying is at 100°C-300°C for 4-8 h, optionally at 150°C-200°C, and / or the sintering is at 500°C-800°C for 4-10 h under inert gas protection, optionally at 650°C-800°C.
[0124] In some embodiments, the sintering temperature in the coating step is 500-800° C. and the sintering time is 4-10 h.
[0125] The manufacturing method of the present application is not particularly limited to the origin of the material. The origin of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, organic acid salt, oxide and hydroxide, provided that the origin can achieve the purpose of the manufacturing method of the present application.
[0126] In some embodiments, the source of element A is one or more selected from the group consisting of element A's elemental, sulfates, halides, nitrates, organic acid salts, oxides, and hydroxides, and / or the source of element R is one or more selected from element R's elemental, sulfates, halides, nitrates, organic acid salts, oxides, hydroxides, and inorganic acids of element R.
[0127] In some embodiments, the source of element M is one or more selected from the group consisting of an elemental salt, a carbonate, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of element M.
[0128] In some embodiments, the source of element M' is one or more selected from the element M', carbonate, sulfate, halide, nitrate, organic acid salt, oxide, and hydroxide.
[0129] The amount of each of the sources of the elements A, R, M, and M' added depends on the target doping amount, and the ratio of the amount of the lithium source, the manganese source, and the phosphorus source used is in accordance with the stoichiometric ratio.
[0130] In the present application, the manganese source may be any manganese-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the manganese source may be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.
[0131] In the present application, the acid may be one or more selected from inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, silicic acid, silicous acid, and organic acids, such as oxalic acid. In some embodiments, the acid is a dilute organic acid having a concentration of 60% by weight or less.
[0132] In the present application, the alkali is one or more selected from sodium hydroxide, potassium hydroxide, aqueous ammonia, and an organic base.
[0133] In the present application, the lithium source may be any lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the lithium source may be one or more selected from lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.
[0134] In the present application, the phosphorus source may be any phosphorus-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.
[0135] In the present application, by way of example, the carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, citric acid.
[0136] In the present application, as an example, the Ni salt is one or more selected from Ni carbonates, sulfates, phosphates, nitrates and organic acid salts.
[0137] In the present application, as an example, the Co salt is one or more selected from Co carbonates, sulfates, phosphates, nitrates and organic acid salts.
[0138] [Positive electrode plate] The positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the above-mentioned positive electrode active material or the positive electrode active material produced by the above-mentioned method.
[0139] For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0140] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0141] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0142] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0143] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.
[0144] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0145] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0146] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0147] In some embodiments, the negative electrode active material may be a negative electrode active material used in batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone alone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as battery negative electrode active materials may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0148] In some embodiments, the negative electrode membrane layer further optionally includes an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS), for example.
[0149] In some embodiments, the negative electrode film layer further optionally includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0150] In some embodiments, the negative electrode membrane layer may further optionally include other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0151] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0152] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative plates. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0153] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0154] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0155] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0156] In some embodiments, the electrolyte solution may further include additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, and the like.
[0157] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.
[0158] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, without any particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without any particular limitation.
[0159] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.
[0160] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.
[0161] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0162] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 2 shows a secondary battery 5 having a rectangular structure as an example.
[0163] In some embodiments, referring to FIG. 3, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art can select it according to the actual needs.
[0164] In some embodiments, the secondary batteries may be assembled into a battery module. The number of secondary batteries included in the battery module may be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0165] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0166] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0167] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.
[0168] 5 and 6 show an example of a battery pack 1. Referring to Fig. 5 and Fig. 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0169] The present application further provides a power consuming device. The power consuming device includes at least one of the secondary battery, the battery module, or the battery pack according to the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0170] As the power consuming device, a secondary battery, a battery module, or a battery pack can be selected according to the usage demand.
[0171] 7 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the secondary battery of the power consumption device.
[0172] [Example] The following describes the preparation examples of the present application. The preparation examples described below are illustrative and are used only to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the preparation examples, they are carried out according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market.
[0173] Preparation of the first positive electrode active material Manufacturing example A3: LiNi 0.55 Co 0.113 Mn 0.277 Al 0.04 Mg 0.02 O2 (single crystal-like) (1) Prepare a mixed solution of NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.55:0.113:0.277 by adding water. The concentration of NiSO4 in the mixed solution is 2 mol / L. Prepare a 5 mol / L NaOH solution. (2) 50L of the mixed solution was introduced into the reaction tank, and then 50L of NaOH solution and an appropriate amount of 0.5mol / L ammonia aqueous solution were introduced into the reaction tank. The pH value in the reaction tank was set to 9.0-12.0, the reaction temperature was set to 40℃-80℃, and the stirring rotation speed was set to 300-1000r / min for 60h. After the reaction was completed, the precipitate was filtered and washed. The washed precipitate was vacuum dried at 120℃ for 24h to obtain a precursor. (3) Li2CO3, precursor, Al2O3 and MgO were mixed. Here, the molar ratio of Li2CO3 (in terms of the molar amount of Li element), precursor (in terms of the total molar amount of the three elements Ni, Co and Mn in the mixed solution), Al2O3 (in terms of the molar amount of Al element) and MgO was 1.05:0.94:0.04:0.02. After mixing, it was placed in a ball mill tank and ball milled at a rotation speed of 300 r / s for 2 hours. It was then placed in a van-type furnace and pre-sintered by heating to 950°C in an air atmosphere of 0.2 MPa and keeping the temperature for 12 hours. The heating rate was 1°C / min. Then, the temperature was lowered to 600°C at a rate of 1°C / min and kept at that temperature for 8 hours. After sintering, the temperature was lowered to 300°C at a rate of 1°C / min and then naturally cooled to room temperature. Then, it was sintered in an air flow mill at a rotation speed of 3000 r / min and 500 m 3 The mixture was pulverized at an air flow rate of 100 / h for 0.5 hours, and then sieved through a 500 mesh screen to obtain a first positive electrode active material.
[0174] Manufacturing example A16: LiNi 0.83 Co 0.114 Mn 0.006 Al 0.04 Mg 0.01 O2 (polycrystalline) (1) A mixed solution was prepared by adding water to NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.83:0.114:0.006. The concentration of NiSO4 in the mixed solution was 2 mol / L. A 6 mol / L NaOH solution was prepared. (2) 50 L of the mixed solution was introduced into the reaction tank, and then 50 L of NaOH solution and an appropriate amount of 0.5 mol / L ammonia aqueous solution were introduced into the reaction tank. The pH value in the reaction tank was set to 10-13, the reaction temperature was set to 40°C-80°C, and the stirring rotation speed was set to 150-300 r / min, and the reaction was carried out for 8-20 hours. After the reaction was completed, the precipitate was filtered and washed. The washed precipitate was vacuum dried at 120°C for 24 hours to obtain a precursor. (3) LiOH, precursor, Al2O3 and MgO were mixed. Here, the molar ratio of LiOH, precursor (converted to the total molar amount of the three elements Ni, Co and Mn in the mixed solution), Al2O3 (converted to the molar amount of Al element) and MgO was 1.05:0.95:0.04:0.01. After mixing, it was placed in a ball mill tank and ball milled at a rotation speed of 500 r / s for 2 h. It was then placed in a van-type furnace and pre-sintered by heating to 750 °C in an air atmosphere of 0.2 MPa and keeping the temperature for 20 h. The temperature rise rate was 20 °C / min. After sintering, the temperature was lowered to 300 °C at a rate of 1 °C / min and then naturally cooled to room temperature. It was crushed for 5 h at a rotation speed of 2000 r / min. The mixture was then heated to 400 °C at a temperature rise rate of 20 °C / min and kept at that temperature for 20 h for sintering. After sintering, the temperature was lowered to 300°C at a rate of 1°C / min, and then the mixture was naturally cooled to room temperature. Then, it was crushed in an airflow mill at a rotation speed of 3000 r / min for 500 m. 3 The mixture was crushed for 0.5 hours at an air flow rate of 100 / h, and then sieved through a 400 mesh screen to obtain a first positive electrode active material.
[0175] Manufacturing Examples A1, A2, A4 to A15, A17 to A22 and Comparative Manufacturing Example A1 The first positive electrode active materials of Production Examples A1, A2, A4 to A11, A22 and Comparative Production Example A1 were produced in the same manner as Production Example A3. See Table 1 for differences in the production, and the rest were the same as Production Example A3. Manufacturing Examples A12 to A15 and A17 to A21 were produced in the same manner as Manufacturing Example A16. See Table 1 for differences in the production, and the rest are the same as Manufacturing Example A16.
[0176] [Table 1] JPEG0007634789000002.jpg237169 JPEG0007634789000003.jpg113169
[0177] Preparation of second positive electrode active material Manufacturing example B1-1 (1) Preparation of co-doped lithium manganese phosphate cores Preparation of manganese oxalate co-doped with Fe, Co and V: 689.5g of manganese carbonate (MnCO3 equivalent, the same below), 455.2g of ferrous carbonate (FeCO3 equivalent, the same below), 4.6g of cobalt sulfate (CoSO4 equivalent, the same below) and 4.9g of vanadium dichloride (VCl2 equivalent, the same below) were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reaction vessel, and 5L of deionized water and 1260.6g of oxalic acid dihydrate (C2H2O4.2H2O equivalent, the same below) were added. The reaction vessel was heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours until the reaction was terminated (no more bubbles were generated), to obtain a manganese oxalate suspension co-doped with Fe, Co, V and S. The suspension was then filtered, and the cake was dried at 120°C and then crushed. Fe, Co and V co-doped manganese oxalate dihydrate particles were obtained with a median particle size Dv50 of 100 nm.
[0178] Preparation of lithium manganese phosphate co-doped with Fe, Co, V and S: The manganese oxalate dihydrate particles obtained in the previous step (1793.4 g), 369.0 g of lithium carbonate (Li2CO3 equivalent, the same below), 1.6 g of dilute sulfuric acid with a concentration of 60% (60% H2SO4 equivalent, the same below) and 1148.9 g of ammonium dihydrogen phosphate (NH4H2PO4 equivalent, the same below) were added to 20 L of deionized water, and the mixture was stirred for 10 hours to mix uniformly, obtaining a slurry. The slurry was transferred to a spray drying device and spray-dried and granulated, and the drying temperature was set to 250 °C and dried for 4 hours to obtain a powder material. In a nitrogen gas (90 vol%) + hydrogen gas (10 vol%) protective atmosphere, the above powder material was sintered at 700 °C for 4 hours to obtain 1572.1 g of lithium manganese phosphate co-doped with Fe, Co, V and S.
[0179] (2) Manufacturing of lithium iron pyrophosphate and lithium iron phosphate Preparation of lithium iron pyrophosphate powder: 4.77g of lithium carbonate, 7.47g of ferrous carbonate, 14.84g of ammonium dihydrogen phosphate, and 1.3g of oxalic acid dihydrate were dissolved in 50ml of deionized water. The pH of the mixture was adjusted to 5, and the mixture was stirred for 2 hours to allow the reaction mixture to react fully. The reaction solution was then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 650°C in a nitrogen gas atmosphere for 8 hours, naturally cooled to room temperature, and then pulverized to obtain Li2FeP2O7 powder.
[0180] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.8 g ferrous carbonate, 34.5 g ammonium dihydrogen phosphate, 1.3 g oxalic acid dihydrate, and 74.6 g sucrose (C 12 H 22 O 11 (converted into 150 ml of deionized water, the same applies below) was dissolved in 150 ml of deionized water to obtain a mixture. The mixture was then stirred for 6 hours to allow the mixture to react sufficiently. The solution after the reaction was then heated to 120°C and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4.
[0181] (3) Covering 1572.1g of the Fe, Co, V and S co-doped lithium manganese phosphate and 15.72g of the LiFePO4 lithium pyrophosphate powder were added to the LiFePO4 suspension obtained in the previous step, and the mixture was stirred to homogeneity, then transferred to a vacuum oven and dried at 150°C for 6 hours. The product was then dispersed using a sand mill. After dispersion, the product was sintered at 700°C for 6 hours in a nitrogen gas atmosphere to obtain the target product, which was a bilayer-coated lithium manganese phosphate.
[0182] Manufacturing example B1-2~Manufacturing example B1-6 In the process of producing the co-doped lithium manganese phosphate core, vanadium dichloride and cobalt sulfate were not used, and instead 463.4 g of ferrous carbonate, 1.6 g of 60% dilute sulfuric acid, 1148.9 g of ammonium dihydrogen phosphate, and 369.0 g of lithium carbonate were used. Except for this, the production conditions of the lithium manganese phosphate core in Production Example B1-2 to Production Example B1-6 were the same as those in Production Example B1-1.
[0183] In the manufacturing process of lithium iron pyrophosphate and lithium iron phosphate and the coating process of the first coating layer and the second coating layer, the raw materials used were adjusted according to the ratio of the coating amount shown in Table 4 to the coating amount corresponding to Manufacturing Example B1-1. The amounts of Li2FeP2O7 / LiFePO4 used in Manufacturing Examples B1-2 to B1-6 were 12.6g / 37.7g, 15.7g / 47.1g, 18.8g / 56.5g, 22.0 / 66.0g, and 25.1g / 75.4g, respectively, and the amount of sucrose used in Manufacturing Examples B1-2 to B1-6 was 37.3g, except that the other conditions were the same as Manufacturing Example B1-1.
[0184] Manufacturing example B1-7~Manufacturing example B1-10 The conditions of Production Examples B1-7 to B1-10 were the same as those of Production Example B1-3, except that the amounts of sucrose used were 74.6 g, 149.1 g, 186.4 g, and 223.7 g, respectively, and the corresponding coating amounts of the second coating layer, the carbon layer, were 31.4 g, 62.9 g, 78.6 g, and 94.3 g, respectively.
[0185] Manufacturing example B1-11 ~ Manufacturing example B1-14 During the production of lithium iron pyrophosphate and lithium iron phosphate, the amounts of various raw materials used were adjusted according to the coating amounts shown in Table 1 to make the amounts of Li2FeP2O7 / LiFePO4 used 23.6g / 39.3g, 31.4g / 31.4g, 39.3g / 23.6g, and 47.2g / 15.7g, respectively. Except for this, the conditions of Production Example B1-11 to Production Example B1-14 were the same as those of Production Example B1-7.
[0186] Manufacturing example B1-15 The conditions for Preparation Example B1-15 were the same as Preparation Example B1-14, except that 492.80 g of ZnCO3 was used instead of ferrous carbonate during the preparation of the co-doped lithium manganese phosphate core.
[0187] Manufacturing example B1-16 ~ Manufacturing example B1-18 The conditions of Production Examples B1-17 to B1-19 were the same as those of Production Example B1-7, except that 466.4 g of NiCO3, 5.0 g of zinc carbonate, and 7.2 g of titanium sulfate were used instead of ferrous carbonate in the preparation of the co-doped lithium manganese phosphate core in Production Example B1-16, 455.2 g of ferrous carbonate and 8.5 g of vanadium dichloride were used in the preparation of the co-doped lithium manganese phosphate core in Production Example B1-17, and 455.2 g of ferrous carbonate, 4.9 g of vanadium dichloride, and 2.5 g of magnesium carbonate were used in the preparation of the co-doped lithium manganese phosphate core in Production Example B1-18.
[0188] Manufacturing example B1-19 ~ Manufacturing example B1-20 The conditions of Production Example B1-19 to Production Example B1-20 were the same as those of Production Example B1-18, except that 369.4 g of lithium carbonate and 1.05 g of 60% dilute nitric acid were used instead of dilute sulfuric acid during the preparation of the co-doped lithium manganese phosphate core in Production Example B1-19, and 369.7 g of lithium carbonate and 0.78 g of silicic acid were used instead of dilute sulfuric acid during the preparation of the co-doped lithium manganese phosphate core in Production Example B1-20.
[0189] Manufacturing example B1-21 ~ Manufacturing example B1-22 The conditions of Production Example B1-21 to Production Example B1-22 were the same as those of Production Example B1-20, except that 632.0 g of manganese carbonate, 463.30 g of ferrous carbonate, 30.5 g of vanadium dichloride, 21.0 g of magnesium carbonate, and 0.78 g of silicic acid were used in the preparation of the co-doped lithium manganese phosphate core in Production Example B1-21, and 746.9 g of manganese carbonate, 289.6 g of ferrous carbonate, 60.9 g of vanadium dichloride, 42.1 g of magnesium carbonate, and 0.78 g of silicic acid were used in the preparation of the co-doped lithium manganese phosphate core in Production Example B1-22.
[0190] Manufacturing example B1-23 ~ Manufacturing example B1-24 In the preparation of the co-doped lithium manganese phosphate core in Preparation Example B1-23, 804.6 g of manganese carbonate, 231.7 g of ferrous carbonate, 1156.2 g of ammonium dihydrogen phosphate, 1.2 g of boric acid (mass fraction 99.5%) and 370.8 g of lithium carbonate were used, and in the preparation of the co-doped lithium manganese phosphate core in Preparation Example B1-24, 862.1 g of manganese carbonate, 173.8 g of ferrous carbonate, 1155.1 g of ammonium dihydrogen phosphate, 1.86 g of boric acid (mass fraction 99.5%) and 371.6 g of lithium carbonate were used. The conditions of Preparation Examples B1-23 to B1-24 are the same as those of Preparation Example B1-22.
[0191] Manufacturing example B1-25 The conditions for Preparation B1-25 were the same as those for Preparation B1-20, except that 370.1 g of lithium carbonate, 1.56 g of silicic acid and 1147.7 g of ammonium dihydrogen phosphate were used during the preparation of the co-doped lithium manganese phosphate core in Preparation B1-25.
[0192] Manufacturing example B1-26 The conditions of Preparation Example B1-26 are the same as those of Preparation Example B1-20, except that 368.3 g of lithium carbonate, 4.9 g of dilute sulfuric acid with a mass fraction of 60%, 919.6 g of manganese carbonate, 224.8 g of ferrous carbonate, 3.7 g of vanadium dichloride, 2.5 g of magnesium carbonate and 1146.8 g of ammonium dihydrogen phosphate were used during the preparation of the co-doped lithium manganese phosphate core in Preparation Example B1-26.
[0193] Manufacturing example B1-27 The conditions of Preparation Example B1-27 are the same as those of Preparation Example B1-20, except that 367.9 g of lithium carbonate, 6.5 g of dilute sulfuric acid with a concentration of 60% and 1145.4 g of ammonium dihydrogen phosphate were used during the preparation of the co-doped lithium manganese phosphate core in Preparation Example B1-27.
[0194] Manufacturing example B1-28 ~ Manufacturing example B1-33 In the preparation of the co-doped lithium manganese phosphate cores in Preparation Example B1-28 to Preparation Example B1-33, 1034.5 g of manganese carbonate, 108.9 g of ferrous carbonate, 3.7 g of vanadium dichloride, and 2.5 g of magnesium carbonate were used, and the amounts of lithium carbonate used were 367.6 g, 367.2 g, 366.8 g, 366.4 g, 366.0 g, and 332.4 g, respectively. The conditions of Production Examples B1-28 to B1-33 were the same as those of Production Example B1-20, except that the amounts of ammonium dihydrogen phosphate used were 1144.5 g, 1143.4 g, 1142.2 g, 1141.1 g, 1139.9 g, and 1138.8 g, respectively, and the amounts of dilute sulfuric acid with a concentration of 60% used were 8.2 g, 9.8 g, 11.4 g, 13.1 g, 14.7 g, and 16.3 g, respectively.
[0195] Manufacturing example B1-34 Core Li 1.1 Mn 0.6 Fe 0.393 Mg 0.007 P 0.9 S 0.1 O4 Production: Preparation of manganese oxalate co-doped with Fe and Mg: 689.5 g of manganese carbonate (MnCO3 equivalent, the same below), 455.2 g of ferrous carbonate (FeCO3 equivalent, the same below), and 5.90 g of magnesium carbonate (MgCO3 equivalent, the same below) were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reaction vessel, and 5 L of deionized water and 1260.6 g of oxalic acid dihydrate (C2H2O4.2H2O equivalent, the same below) were added. The reaction vessel was heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours until the reaction was terminated (no more bubbles were generated), to obtain a manganese oxalate suspension co-doped with Fe and Mg. The suspension was then filtered, and the cake was dried at 120°C and then pulverized. Manganese oxalate dihydrate particles co-doped with Fe and Mg were obtained with a median particle size Dv50 of 100 nm.
[0196] Preparation of lithium manganese phosphate co-doped with Fe, Mg and Si: The manganese oxalate dihydrate particles (1791.3 g) obtained in the previous step, 406.3 g of lithium carbonate (Li2CO3 equivalent, the same below), 7.8 g of silicic acid (H2SiO3 equivalent, the same below) and 1035.0 g of ammonium dihydrogen phosphate (NH4H2PO4 equivalent, the same below) were added to 20 L of deionized water, and the mixture was stirred for 10 hours to mix uniformly, obtaining a slurry. The slurry was transferred to a spray drying device for spray drying granulation, and the drying temperature was set to 250 °C and dried for 4 hours to obtain a powder material. In a nitrogen gas (90 vol%) + hydrogen gas (10 vol%) protective atmosphere, the above powder material was sintered at 700 °C for 4 hours to obtain 1574.0 g of lithium manganese phosphate co-doped with Fe, Mg and Si.
[0197] For other conditions, see Production Example B1-1.
[0198] Manufacturing example B1-35 Core LiMn 0.50 Fe 0.50 P 0.995 N 0.005 Manufacturing of O4.
[0199] Preparation of Fe-doped manganese oxalate: 574.7g of manganese carbonate (MnCO3 equivalent, the same below) and 579.27g of ferrous carbonate (FeCO3 equivalent, the same below) were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reaction vessel, and 5L of deionized water and 1260.6g of oxalic acid dihydrate (C2H2O4.2H2O equivalent, the same below) were added. The reaction vessel was heated to 80°C and stirred at a rotation speed of 600 rpm for 6 hours until the reaction was terminated (no more bubbles were generated), to obtain a Fe-doped manganese oxalate suspension. The suspension was then filtered, and the cake was dried at 120°C and then pulverized. Fe-doped manganese oxalate dihydrate particles with a median particle size Dv50 of 100 nm were obtained.
[0200] Preparation of lithium manganese phosphate co-doped with Fe and N: The manganese oxalate dihydrate particles (1794.4 g) obtained in the previous step, 369.4 g of lithium carbonate (converted to Li2CO3, the same below), 5.25 g of dilute nitric acid (converted to 60% HNO3, the same below) and 1144.3 g of ammonium dihydrogen phosphate (converted to NH4H2PO4, the same below) were added to 20 L of deionized water, and the mixture was stirred for 10 hours to mix uniformly, obtaining a slurry. The slurry was transferred to a spray drying device and spray-dried and granulated, and the drying temperature was set to 250 °C and dried for 4 hours to obtain a powder material. In a nitrogen gas (90 vol%) + hydrogen gas (10 vol%) protective atmosphere, the above powder material was sintered at 700 °C for 4 hours to obtain 1572.2 g of lithium manganese phosphate co-doped with Fe and N.
[0201] For other conditions, see Production Example B1-1.
[0202] Manufacturing example B1-36 Core LiMn 0.909 Fe 0.091 P 0.99 N 0.01The same as in Production Example B1-1, except that 1044.6 g of manganese carbonate, 1138.5 g of ammonium dihydrogen phosphate, and 369.4 g of lithium carbonate were used when producing O4, and 105.4 g of ferrous carbonate and 10.5 g of dilute nitric acid (60% HNO3 equivalent, the same below) were additionally added.
[0203] Manufacturing example B1-37 Core LiMn 0.091 Fe 0.909 P 0.995 N 0.005 The same as in Production Example B1-1, except that 104.5 g of manganese carbonate, 1138.5 g of ammonium dihydrogen phosphate, and 371.3 g of lithium carbonate were used when producing O4, and 1052.8 g of ferrous carbonate and 5.25 g of dilute nitric acid (60% HNO3 equivalent, the same below) were additionally added.
[0204] Manufacturing example B1-38 In the manufacturing process of lithium iron pyrophosphate and lithium iron phosphate and the coating process of the first coating layer and the second coating layer, the raw materials used were adjusted according to the ratio of the coating amount shown in Table 4 to the coating amount corresponding to Manufacturing Example B1-1, and the amounts of Li2FeP2O7 / LiFePO4 used were 62.9 g / 47.1 g, respectively. Other conditions were the same as in Example 1-1.
[0205] Manufacturing example B1-39 In the preparation of silver pyrophosphate, 463.4g of silver oxide (Ag2O equivalent, the same below) and 230.6g of phosphoric acid (85% H3PO4 equivalent, the same below) were thoroughly mixed. It was heated to 450°C and stirred continuously for 2 hours to allow the reaction mixture to react thoroughly. The reaction solution was then kept at 450°C for 4 hours to obtain a viscous paste containing Ag4P2O7. It eventually turned into a solid and was washed with deionized water. The resulting product was ground in a ball mill filled with ethanol for 4 hours, and the resulting product was dried under an infrared lamp to obtain Ag4P2O7 powder. The rest was the same as in Preparation Example B1-1.
[0206] Manufacturing example B1-40 The process for preparing lithium manganese phosphate co-doped with Fe, Co, V and S was the same as Preparation Example B1-21, except that the powder material was sintered at 650°C for 43.5 hours in a protective atmosphere of nitrogen gas (90% by volume) + hydrogen gas (10% by volume).
[0207] Manufacturing example B2-1 During the production of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step was set to 550°C, the sintering time was set to 1 hour, and the crystallinity of Li2FeP2O7 was controlled to 30%. During the production of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was set to 650°C, the sintering time was set to 2 hours, and the crystallinity of LiFePO4 was controlled to 30%. Other conditions were the same as those in Production Example B1-1.
[0208] Manufacturing example B2-2 During the production of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step was set to 550°C, the sintering time was set to 2 hours, and the crystallinity of Li2FeP2O7 was controlled to 50%. During the production of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was set to 650°C, the sintering time was set to 3 hours, and the crystallinity of LiFePO4 was controlled to 50%. Other conditions were the same as those in Production Example B1-1.
[0209] Manufacturing example B2-3 During the production of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step was set to 600°C, the sintering time was set to 3 hours, and the crystallinity of Li2FeP2O7 was controlled to 70%. During the production of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was set to 650°C, the sintering time was set to 4 hours, and the crystallinity of LiFePO4 was controlled to 70%. Other conditions were the same as those in Production Example B1-1.
[0210] Manufacturing example B2-4 During the production of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step was set to 650°C, the sintering time was set to 4 hours, and the crystallinity of Li2FeP2O7 was controlled to 100%, and during the production of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was set to 700°C, the sintering time was set to 6 hours, and the crystallinity of LiFePO4 was controlled to 100%, except that the other conditions were the same as those of Production Example B1-1.
[0211] Manufacturing Example B3-1 to Manufacturing Example B3-12 In the process of producing manganese oxalate particles co-doped with Fe, Co and V, the heating temperature / stirring time in the reaction tank of Production Example B3-1 was 60°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-2 was 70°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-3 was 80°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-4 was 90°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-5 was 100°C / 120 minutes, and the heating temperature / stirring time in the reaction tank of Production Example B3-6 was 110°C / 120 minutes. The heating temperature / stirring time in the reaction tank of Production Example B3-7 is 120°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-8 is 130°C / 120 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-9 is 100°C / 60 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-10 is 100°C / 90 minutes, the heating temperature / stirring time in the reaction tank of Production Example B3-11 is 100°C / 150 minutes, and the heating temperature / stirring time in the reaction tank of Production Example B3-12 is 100°C / 180 minutes, except that the other conditions of Production Examples B3-1 to B3-12 are the same as those of Production Example B1-1.
[0212] Manufacturing example B4-1 ~ Manufacturing example B4-4 The drying temperature / drying time in the drying step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) was 100°C / 4h, 150°C / 6h, 200°C / 6h and 200°C / 6h, respectively, and the sintering temperature and sintering time in the sintering step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) was 700°C / 6h, 700°C / 6h, 700°C / 6h and 600°C / 6h, respectively. The other conditions were the same as those of Preparation Example B1-7.
[0213] Manufacturing example B4-5 ~ Manufacturing example B4-7 Except that the drying temperature / drying time in the drying step during the coating process was 150°C / 6h, 150°C / 6h and 150°C / 6h, respectively, and the sintering temperature and sintering time in the sintering step during the coating process was 600°C / 4h, 600°C / 6h and 800°C / 8h, respectively, the other conditions were the same as those of Preparation Example B1-12.
[0214] Comparative manufacturing example B1 Preparation of manganese oxalate: 1149.3g of manganese carbonate was added to a reaction vessel, and 5L of deionized water and 1260.6g of oxalic acid dihydrate (C2H2O4·2H2O equivalent, the same below) were added. The reaction vessel was heated to 80℃ and stirred at a rotation speed of 600 rpm for 6 hours until the reaction was completed (no more bubbles were generated), to obtain a manganese oxalate suspension. The suspension was then filtered, and the cake was dried at 120℃ and then crushed to obtain manganese oxalate dihydrate particles with a median particle size Dv50 of 100nm.
[0215] Preparation of carbon-coated lithium manganese phosphate: 1789.6 g of the manganese oxalate dihydrate particles obtained above, 369.4 g of lithium carbonate (converted to Li2CO3, the same applies below), 1150.1 g of ammonium dihydrogen phosphate (converted to NH4H2PO4, the same applies below), and 31 g of sucrose (C 12 H 22 O 11The 100% sintered powder was added to 20 L of deionized water, and the mixture was stirred for 10 hours to mix uniformly, to obtain a slurry. The slurry was transferred to a spray drying machine and spray-dried and granulated, and the drying temperature was set to 250°C and dried for 4 hours to obtain a powder material. The powder material was sintered at 700°C for 4 hours in a nitrogen gas (90% by volume) + hydrogen gas (10% by volume) protective atmosphere to obtain carbon-coated lithium manganese phosphate.
[0216] Comparative manufacturing example B2 Except for using 689.5 g of manganese carbonate and additionally adding 463.3 g of ferrous carbonate, the other conditions of Comparative Production Example B2 are the same as those of Comparative Production Example B1.
[0217] Comparative manufacturing example B3 Except for using 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate, and additionally adding 1.6 g of 60% dilute sulfuric acid, the other conditions of Comparative Preparation Example B3 are the same as those of Comparative Preparation Example B1.
[0218] Comparative manufacturing example B4 Except for using 689.5 g of manganese carbonate, 1148.9 g of ammonium dihydrogen phosphate, and 369.0 g of lithium carbonate, and additionally adding 463.3 g of ferrous carbonate and 1.6 g of 60% dilute sulfuric acid, the other conditions of Comparative Preparation Example B4 are the same as those of Comparative Preparation Example B1.
[0219] Comparative manufacturing example B5 Except for the following additional steps, when preparing the lithium iron pyrophosphate powder, 9.52g of lithium carbonate, 29.9g of ferrous carbonate, 29.6g of ammonium dihydrogen phosphate, and 32.5g of oxalic acid dihydrate were dissolved in 50ml of deionized water. The pH of the mixture was adjusted to 5, and the mixture was stirred for 2 hours to allow the reaction mixture to react fully. The reaction solution was then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 500°C in a nitrogen gas atmosphere for 4 hours, and then naturally cooled to room temperature and crushed to control the crystallinity of Li2FeP2O7 to 5%. Except for the amount of Li2FeP2O7 used for preparing the carbon-coated material, which was 62.8g, the other conditions of Comparative Preparation Example B5 were the same as those of Comparative Preparation Example B4.
[0220] Comparative manufacturing example B6 Except for the following additional step, when preparing the lithium iron phosphate suspension, 14.7g of lithium carbonate, 46.1g of ferrous carbonate, 45.8g of ammonium dihydrogen phosphate, and 50.2g of oxalic acid dihydrate were dissolved in 500ml of deionized water, and the mixture was thoroughly reacted by stirring for 6 hours. The temperature of the reacted solution was then raised to 120°C and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4. During the preparation of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was 600°C, the sintering time was 4h, and the crystallinity of LiFePO4 was controlled to 8%, and the amount of LiFePO4 used in preparing the carbon-coated material was 62.8g. The other conditions of Comparative Preparation Example B6 were the same as those of Comparative Preparation Example B4.
[0221] Comparative manufacturing example B7 Preparation of lithium iron pyrophosphate powder: 2.38g of lithium carbonate, 7.5g of ferrous carbonate, 7.4g of ammonium dihydrogen phosphate, and 8.1g of oxalic acid dihydrate were dissolved in 50ml of deionized water. The pH of the mixture was adjusted to 5, and the mixture was stirred for 2 hours to allow the reaction mixture to react fully. The reaction solution was then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 500°C in a nitrogen gas atmosphere for 4 hours, and then naturally cooled to room temperature, and then pulverized to control the crystallinity of Li2FeP2O7 to 5%.
[0222] Preparation of lithium iron phosphate suspension: 11.1 g lithium carbonate, 34.7 g ferrous carbonate, 34.4 g ammonium dihydrogen phosphate, 37.7 g oxalic acid dihydrate, and 37.3 g sucrose (C 12 H 22 O 11 The mixture was thoroughly reacted by stirring for 6 hours. The temperature of the reacted solution was then raised to 120°C and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4.
[0223] The obtained lithium iron pyrophosphate powder 15.7 was added to the lithium iron phosphate (LiFePO4) and sucrose suspension, and the sintering temperature in the coating sintering step during the production was set to 600°C, the sintering time was set to 4 hours, and the crystallinity of LiFePO4 was controlled to 8%. Except for this, the other conditions of Comparative Production Example B7 were the same as those of Comparative Production Example B4, and a positive electrode active material coated with amorphous lithium iron pyrophosphate, amorphous lithium iron phosphate, and carbon was obtained.
[0224] Comparative manufacturing examples B8~B11 The drying temperature / drying time in the drying step during the production of lithium iron pyrophosphate (Li2FeP2O7) was 80°C / 3h, 80°C / 3h, and 80°C / 3h in Comparative Preparation Examples B8 to B10, the sintering temperature and sintering time in the sintering step during the production of lithium iron pyrophosphate (Li2FeP2O7) were 400°C / 3h, 400°C / 3h, and 350°C / 2h in Comparative Preparation Examples B8 to B10, and the drying temperature / drying time in the drying step during the production of lithium iron phosphate (LiFePO4) in Comparative Preparation Example B11 was 80°C / 3h, and the amounts of Li2FeP2O7 / LiFePO4 used in Comparative Preparation Examples B8 to B11 were 47.2g / 15.7g, 15.7g / 47.2g, 62.8g / 0g, and 0g / 62.8g, respectively, except that the other conditions were the same as those of Preparation Examples B1 to B7.
[0225] Manufacturing of mixed positive electrode active material Examples 1 to 43 and Comparative Examples 1 to 2 The first positive electrode active material and the second positive electrode active material were mixed in a stirring tank by stirring, and the mass of the first positive electrode active material was m1 and the mass of the second positive electrode active material was m2. The mass of the mixed positive electrode active material was m1 + m2.
[0226] The parameters of each of the examples and comparative examples are shown in Table 2.
[0227] [Table 2] JPEG0007634789000005.jpg178166
[0228] Full battery production The positive electrode active material, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive were mixed uniformly in an N-methylpyrrolidone solvent system in a weight ratio of 92:2.5:5.5. The mixture was then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode plate. The coating amount was 0.4 g / cm. 2 and the compaction density is 2.4g / cm 3 It is.
[0229] The negative electrode active materials, artificial graphite, hard carbon, conductive agent acetylene black, adhesive agent styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC), were mixed uniformly in deionized water in a weight ratio of 90:5:2:2:1. The mixture was then coated on copper foil, dried, and cold pressed to obtain a negative electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 1.7 g / cm 3 It is.
[0230] A polyethylene (PE) porous polymer film was used as a separator, and a positive electrode plate, a separator, and a negative electrode plate were stacked in order so that the separator was located in the center of the positive and negative electrodes to play the role of isolation, and then wound to obtain a bare cell. The bare cell was placed in an exterior body, and the same electrolyte as that used in manufacturing the button cell was injected and packaged to obtain a full battery (hereinafter also referred to as a "full cell").
[0231] Button battery manufacturing The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black were added to N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and the mixture was stirred in a drying chamber to prepare a slurry. The slurry was coated on an aluminum foil, dried, and cold pressed to prepare a positive electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 2.0 g / cm 3 It is.
[0232] A lithium sheet was used as the negative electrode, and 1 mol / L LiPF6 was dissolved in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 as the electrolyte. Together with the positive electrode plate manufactured above, this was assembled into a button cell box as a button battery (hereinafter also referred to as a "button cell").
[0233] The positive electrode active material may be a first positive electrode active material, a second positive electrode active material, or a mixed positive electrode active material.
[0234] Material Performance Testing 1. Measurement of the chemical formula of the positive electrode active material The internal microstructure and surface structure of the positive active material were characterized with high spatial resolution using a spherical aberrometer (ACSTEM), and combined with three-dimensional reconstruction technology to obtain the core chemical formula of the positive active material and the composition of the two coating layers.
[0235] 2. Lattice change rate measurement method In a constant temperature environment of 25℃, the positive electrode active material sample was placed in an XRD (model number: Bruker D8 Discover), the sample was tested at 1° / min, and the test data was analyzed. Referring to the PDF card of the specification, the lattice constants a0, b0, c0, and v0 (a0, b0, and c0 represent the length size in each direction of the unit lattice, and v0 represents the volume of the unit lattice, which can be obtained directly from the XRD finishing results) were calculated.
[0236] The positive electrode active material was prepared as a button cell according to the above "Preparation of Button Batteries", and the button cell was charged at a low rate of 0.05C until the current decreased to 0.01C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours for immersion. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The lattice constant v1 was calculated in the same manner as the fresh test sample above, and (v0-v1) / v0×100% was shown in the table as the lattice change rate before and after the lithium was completely released.
[0237] 3.Measuring method for Li / Mn antisite defect concentration The XRD results tested using the "Lattice Change Rate Measurement Method" were compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested using the "Lattice Change Rate Measurement Method" were introduced into the General Structure Analysis System (GSAS) software to automatically obtain the refinement results, which included the occupancy status of different atoms, and the Li / Mn antisite defect concentration was obtained by reading the refinement results.
[0238] 4. Surface oxygen valence measurement method 5 g of the positive electrode active material sample was taken and fabricated into a button cell according to the above "Fabrication of Button Batteries". The button cell was charged at a low rate of 0.05 C until the current decreased to 0.01 C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours to soak. It was then dried, the powder was scraped off, and particles with a particle size smaller than 500 nm were selected. The obtained particles were measured by electron energy loss spectroscopy (EELS, the model number of the equipment used was Talos F200S) to obtain the energy loss near edge structure (ELNES), which reflected the state density and energy level distribution of the elements. From the state density and energy level distribution, the valence of the surface oxygen after charging was estimated by integrating the valence band state density data and calculating the number of occupied electrons.
[0239] 5.Method of measuring consolidated density 5 g of the positive electrode active material powder was placed in a compaction mold (CARVER mold, model number 13 mm, USA), and the mold was placed on a compaction density meter. A pressure of 3 T was applied, and the powder thickness at pressure (thickness after decompression) was read on the instrument, and the compaction density was calculated from ρ = m / v.
[0240] 6. Method for measuring the amount of Mn (and Fe doped into Mn sites) dissolved after cycling The positive electrode active material sample was fabricated into a full battery according to "Fabrication of a Full Battery" above. The full battery, which had been cycled at 45°C until the capacity had decayed to 80%, was discharged at a rate of 0.1 C to a cut-off voltage of 2.0 V. The battery was then disassembled, the negative electrode plate was removed, and 30 unit area (1540.25 mm2) pieces were placed on the negative electrode plate. 2 ) wafers were randomly taken and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. Based on the ICP results, the amount of Fe (if Fe is doped on the Mn site of the positive electrode active material) and Mn were calculated, and the amount of Mn (and Fe doped on the Mn site) dissolved after cycling was calculated accordingly. The test standard complies with EPA-6010D-2014.
[0241] 7.Measuring the initial gram capacity of a button battery The button battery was charged at 0.1 C from 2.5 to 4.3 V to 4.3 V, and then charged at a constant voltage of 4.3 V until the current was 0.05 mA or less, left to stand for 5 minutes, and then discharged at 0.1 C to 2.0 V. The discharge capacity at this time was taken as the initial gram capacity and was designated as D0.
[0242] 8.3C constant current charging ratio measurement method In a constant temperature environment of 25°C, a fresh full battery was left standing for 5 min, discharged at 1 / 3C to 2.5V. Left standing for 5 min, charged at 1 / 3C to 4.3V, and then charged at 4.3V with a constant voltage until the current was 0.05mA or less. Left standing for 5 min, the charge capacity at this time was recorded as C0. Discharged at 1 / 3C to 2.5V, left standing for 5 min, charged at 3C to 4.3V, and left standing for 5 min. The charge capacity at this time was recorded as C1. The constant current charging ratio at 3C is C1 / C0 x 100%.
[0243] The higher the charging constant current ratio at 3C, the better the rate performance of the battery.
[0244] 9. Cycle performance test of full battery at 45℃ In a constant temperature environment of 45°C, the full battery was charged at 1C from 2.5 to 4.3V to 4.3V, and then constant voltage charged at 4.3V until the current was 0.05mA or less. It was left to stand for 5min, and then discharged at 1C to 2.5V, and the discharge capacity at this time was recorded as D0. The above charge-discharge cycle was repeated until the discharge capacity decreased to 80% of D0. The number of cycles the battery had gone through was recorded.
[0245] 10. Full battery expansion test at 60℃ The full battery was stored at 60°C with a state of charge (SOC) of 100%. Before, during and after storage, the open circuit voltage (OCV) and internal resistance (IMP) of the cell were measured to monitor the SOC, and the cell volume was also measured. Here, after every 48 hours of storage, the full battery was taken out and left to stand for 1 hour before testing the open circuit voltage (OCV) and internal resistance (IMP). After cooling to room temperature, the cell volume was measured using the drainage method. In the drainage method, the gravity F1 of the cell was measured independently using a balance that automatically converts units using the dial data, and the cell was then completely immersed in deionized water (density 1 g / cm). 3 The gravity F2 of the cell was measured and the buoyancy force acting on the cell was calculated. JPEG0007634789000006.jpg58 is F1-F2, and Archimedes principle Cell volume based on JPEG0007634789000007.jpg634 JPEG0007634789000008.jpg559 was calculated.
[0246] From the results of the OCV and IMP tests, the batteries of the present embodiment maintained an SOC of 99% or more throughout the entire storage period of this experiment.
[0247] After storage for 30 days, the cell volume was measured, and the increase rate of the cell volume after storage relative to the cell volume before storage was calculated.
[0248] The remaining capacity of the cell was also measured. A full battery was charged at 1C from 2.5 to 4.3V up to 4.3V, and then charged at a constant voltage of 4.3V until the current was 0.05mA or less. The battery was left to stand for 5min, and the charge capacity at this time was recorded as the remaining capacity of the cell.
[0249] 11. Specific surface area (BET) measurement method In accordance with GB / T 19587-2004, the specific surface area test was performed on the positive electrode active material using a specific surface area porosity analyzer TRISTAR II 3020 (Micromeritics, USA). Before the test, the positive electrode active material was placed in a vacuum oven and dried at 200°C for ≥2h, with the sample weight >20g.
[0250] 12. Particle size Dv50 test The particle size Dv50 of the positive electrode active material was measured using a Mastersizer 3000 laser diffraction particle size analyzer (Malvern Panalytical) with reference to GB / T19077-2016. Here, deionized water was used as the solvent, and the positive electrode active material was ultrasonicated for 5 min before the test.
[0251] 13. ICP Test (Inductively Coupled Plasma Atomic Emission Spectroscopy) The elemental content test was performed using an iCAP 7400 inductively coupled plasma optical emission spectrometer with reference to EPA 6010D-2014, and aqua regia was selected as the solvent. Formula for calculating powder element content: Element content (mass%) = 100% x element mass / sample mass. Formula for calculating the content of electrode plate elements: Content of element (mass%) = 100% x element mass / (sample mass-current collector mass).
[0252] 14. Li2CO3 and LiOH content test (free lithium potential titration test) The test was carried out using a 905 potentiometer in accordance with GB / T 9736-2008. After sampling, the samples were immediately vacuum sealed in aluminum plastic film bags. The minimum sample size for one test was ≥ 30g.
[0253] 15.Crystal type test Unless otherwise specified, in this application, the terms "single crystal / single crystal-like particles", "quasi-single crystal particles", "single crystal particles", "single crystal material particles" or similar expressions have essentially the same meaning and refer to single particles (i.e., primary particles) and / or agglomerated particles. Among them, agglomerated particles are particles formed by agglomeration of 100 or less (especially about 5 to 50) primary particles having an average particle size in the range of 50 nm to 10,000 nm.
[0254] Unless otherwise specified, in this application, the terms "secondary particles" and "polycrystalline material particles" have generally similar meanings and refer to particles formed by aggregation of more than 100 primary particles having an average particle size in the range of 50-800 nm.
[0255] The positive electrode active material was examined using a scanning electron microscope, the sample and magnification were adjusted so that there were more than 10 aggregate particles in the field of view, the number of primary particles constituting each aggregate particle was counted, and the longitudinal size of the primary particles was measured on a scale to determine the particle size, and the particle size of the primary particles in each aggregate particle was sorted in ascending order. The data with the largest particle size of 1 / 10 and the data with the smallest particle size of 1 / 10 were removed, and the average value of the remaining particle size data was taken to determine the average particle size of the primary particles in this aggregate particle. If the number and average particle size of primary particles in 50% or more (including 50%) of the aggregate particles met the above definition of "polycrystalline material particles," the positive electrode active material was determined to be a polycrystalline material, and if not, it was determined to be a single crystal or single crystal-like material.
[0256] 16. Hot Box Safety Test The test was conducted by referring to the "heating" chapter of the safety test in GB 38031-2020 to find the upper boundary. The optimized test conditions are as follows:
[0257] I. Advance Preparation Test conditions: An explosion-proof oven capable of heating the wiring connection port was prepared. The test cell was a fresh bare cell (cycle count ≦10). Temperature-sensing wires were attached to the periphery of the cell and to the poles, etc., for temperature monitoring, and a temperature recording device was also installed. Cell treatment before testing: Constant current constant voltage charging was performed at a rate current of 0.33C to fully charge the cell to the nominal voltage (for example, in the present invention, the voltage is 4.3V).
[0258] II. Testing Process The sample was placed in a high-temperature bath, and the bath was heated from room temperature to 100°C at 5°C / min, maintained at that temperature for 2 hours, and then further heated at 5°C / min, maintaining each 5°C interval for 30 minutes. The sample was heated until the cell went out of control (runaway standard: voltage drop ≧50% within 1 min, cell temperature increase ≧50% within 1 min) or until the cell reached 200°C, at which point heating was stopped.
[0259] III. Data Processing Based on the above conditions, the failure point was found, and the corresponding temperature and time were obtained. Time@temperature, for example, 21min@150℃.
[0260] IV. Results Benchmark The longer the duration of the test, the greater the safety of the sample. The longer the duration of the test, the greater the safety of the sample. The sample may be a sample with the same failure point temperature but a longer time, a sample with the same failure point time but a higher temperature, or a sample with both a different failure point temperature and time but a higher temperature.
[0261] [Table 3]
[0262] [Table 4] JPEG0007634789000011.jpg237169 JPEG0007634789000012.jpg250169 JPEG0007634789000013.jpg74169
[0263] As can be seen from Preparation Examples B1-1 to B1-40 and Comparative Preparation Examples B1 to B4, the presence of the first coating layer is advantageous in reducing the Li / Mn antisite defect concentration of the resulting material and the amount of Fe and Mn dissolved after cycling, improving the gram capacity of the button cell of the battery, and improving the safety performance and cycle performance of the battery. When other elements are doped into the Mn site and the phosphorus site, the lattice change rate, antisite defect concentration, and amount of Fe and Mn dissolved of the resulting material can be significantly reduced, improving the gram capacity of the battery, and improving the safety performance and cycle performance of the battery.
[0264] It can be seen from Preparation Example B1-1 to Preparation Example B1-6 in summary that as the amount of the first coating layer increases from 3.2% to 6.4%, the Li / Mn antisite defect concentration of the obtained material gradually decreases, and the amount of Fe and Mn eluted after cycling gradually decreases. The safety performance and cycle performance at 45°C of the corresponding battery are also improved, but the gram capacity of the button cell is slightly decreased. Alternatively, when the total amount of the first coating layer is 4 to 5.6 wt%, the overall performance of the corresponding battery is optimal.
[0265] It can be seen from Preparation Example B1-3 and Preparation Example B1-7 to Preparation Example B1-10 together that as the amount of the second coating layer increases from 1% to 6%, the Li / Mn antisite defect concentration of the obtained material gradually decreases, and the amount of Fe and Mn eluted after cycling gradually decreases. The safety performance and cycle performance at 45°C of the corresponding battery are also improved, but the gram capacity of the button cell is slightly decreased. Alternatively, when the total amount of the second coating layer is 3 to 5 wt%, the overall performance of the corresponding battery is optimal.
[0266] As can be seen from a combination of Production Examples B1-11 to B1-15 and Comparative Production Examples B5 to B6, when Li2FeP2O7 and LiFePO4 are simultaneously present in the first coating layer, and the weight ratio of Li2FeP2O7 to LiFePO4 is 1:3 to 3:1, and particularly 1:3 to 1:1, the improvement in battery performance is more obvious.
[0267] [Table 5]
[0268] As can be seen from Table 5, with the gradual increase in the crystallinity of pyrophosphate and phosphate in the first coating layer, the lattice change rate of the corresponding materials, the Li / Mn antisite defect concentration and the amount of Fe and Mn dissolved gradually decrease, the button cell capacity of the battery gradually increases, and the safety performance and cycle performance are also gradually improved.
[0269] [Table 6]
[0270] As can be seen from Table 6, by adjusting the reaction temperature and reaction time in the reaction tank during the preparation of manganese oxalate particles, each performance of the positive electrode material of the present application can be further improved. For example, in the process of gradually increasing the reaction temperature from 60°C to 130°C, the lattice change rate and Li / Mn antisite defect concentration first decrease and then increase. The corresponding post-cycle metal elution amount and safety performance also show similar rules, but the button cell capacity and cycle performance first increase and then decrease with increasing temperature. Even if the reaction temperature is controlled to remain constant and the reaction time is adjusted, a similar rule can also be shown.
[0271] [Table 7]
[0272] As can be seen from Table 7, when lithium iron pyrophosphate is produced by the method of the present application, the performance of the obtained material can be improved by adjusting the drying temperature / time and the sintering temperature / time in the production process. This can improve the battery performance. As can be seen from Comparative Production Examples B8 to B11, when the drying temperature in the lithium iron pyrophosphate production process is lower than 100°C or the sintering step temperature is lower than 400°C, Li2FeP2O7, which is desired to be produced in the present application, cannot be obtained. Therefore, the material performance and the performance of the battery including the obtained material cannot be improved.
[0273] [Table 8] JPEG0007634789000018.jpg189169
[0274] What can be seen from Table 8: As can be seen by comparing Examples 1 to 43 with Comparative Example 1, compared to the secondary battery prepared by mixing a first positive electrode active material and a second positive electrode active material not doped with an M element in Comparative Example 1, the secondary battery prepared using the mixed positive electrode active material of the present application had a higher cycle capacity retention rate and a longer cycle life.
[0275] As can be seen by comparing Example 16 with Examples 23 to 29, when the mass relationship m1 / (m1+m2) between the first positive electrode active material and the second positive electrode active material of the present application is between 3% and 50%, the cycle capacity retention rate of the manufactured secondary battery is further improved and the cycle life is further extended.
[0276] b×m of the first positive electrode active material and the second positive electrode active material of the present application 1 / When m1+m2 was 0.457 or less, the cycle capacity retention rate of the manufactured secondary battery was high, the cycle life was long, and the safety was high. As can be seen from a comparison between Example 16 and Examples 23 to 29, when the mass relationship b×m1 / (m1+m2) between the first positive electrode active material and the second positive electrode active material of the present application was within the range of 0.025 to 0.415, the cycle capacity retention rate of the manufactured secondary battery was further improved, the cycle life was further extended, and the safety was further improved.
[0277] As can be seen from a comparison of Examples 1 to 10 and 22, when the first positive electrode active material of the present application is single crystal-like, the D v When the particle size of the first positive electrode active material was 5.8 μm or less, the secondary battery had a high cycle capacity retention rate, a long cycle life, and high safety. v When the particle size was 4.3 μm or less, the cycle capacity retention rate of the secondary battery produced was higher and the cycle life was longer.
[0278] As can be seen from a comparison of Examples 12 to 20, when the first positive electrode active material of the present application is polycrystalline, the D v 50 Particle size is 3.5 to 13.5 μm, and the BET specific surface area is 1.32 m 2 / g or less and the compaction density at 3T pressure is 2.92 g / cm 3 When the temperature was equal to or higher than 100° C., the cycle capacity retention rate of the produced secondary battery was higher and the cycle life was longer.
[0279] As can be seen from a comparison of Examples 1 to 8, 10 to 11, and 22, when the first positive electrode active material of the present application is single crystal-like, the first positive electrode active material LiNi b Co d Mn e M f When d in O2 was selected from the range of 0.047 to 0.320, the cycle capacity retention rate of the produced secondary battery was higher and the cycle life was longer.
[0280] The first positive electrode active material of the present application is LiNi b Co dMn e M f When b in O2 is selected from the range of 0.314 to 0.970, the secondary battery produced has a high cycle capacity retention rate, a long cycle life, and high safety. As can be seen from comparing Examples 1 to 7, 9 to 11, and 22, when the first positive electrode active material is a single crystal or pseudo single crystal material, and b is greater than 0.314 and less than 0.97 (excluding the values of 0.314 and 0.97), the secondary battery produced has a higher cycle capacity retention rate and a longer cycle life.
[0281] As can be seen from the comparison between Examples 10 and 22, when the mass content of lithium carbonate in the first positive electrode active material of the present application is 1% or less and the mass content of lithium hydroxide is 1% or less, the cycle capacity retention rate of the produced secondary battery is higher, the cycle life is longer, and the safety is higher.
[0282] Comparing Table 3 with Table 8 reveals: Compared with the secondary batteries produced using the first positive electrode active material, the secondary batteries produced using the mixed positive electrode active material containing the first positive electrode active material of the present application had higher safety, and compared with the secondary batteries produced using the first positive electrode active materials of Production Examples A5, and A11 to A22, the secondary batteries produced using the mixed positive electrode active material containing the first positive electrode active material of the present application had higher cycle capacity retention and longer cycle life.
[0283] Comparing Tables 4-6 with Table 8 reveals: Compared with the secondary batteries manufactured using the second positive electrode active materials of Manufacturing Examples B1-10, B1-14, B1-33, B2-1, B2-2, B3-1, B3-8, and Manufacturing Examples B1-34 to B1-40, the secondary batteries manufactured using the mixed positive electrode active material containing the corresponding second positive electrode active material of the present application had higher cycle capacity retention rates and longer cycle lives.
[0284] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0285] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate, 11 core, 12 first coating layer, 13 second coating layer.
Claims
1. A positive electrode active material including a first positive electrode active material and a second positive electrode active material, The first positive electrode active material is the compound LiNi b Co d Mn e M' f O 2 Including, Where: The b is selected from the range of 0.314 to 0.970; The d is selected from the range of 0 to 0.320, The e is selected from the range of 0.006 to 0.390, the sum of b, d, e and f is 1, and f is greater than 0; M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S, and Y; the second positive electrode active material includes a core, a first coating layer coating the core, and a second coating layer coating the first coating layer, Where: The core is the compound Li 1+x Mn 1-y A y P 1-z R z O 4 Including, The first coating layer is a pyrophosphate M a P 2 O 7 and Phosphate X n P.O. 4 and the second coating layer comprises carbon; Where: The x is selected from the range of −0.100 to 0.100, The y is selected from the range of 0.001 to 0.909, The z is selected from the range of 0.001 to 0.100, a is greater than 0 and less than or equal to 4; n is greater than 0 and less than or equal to 2; A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge; R is one or more elements selected from B, Si, N and S; The positive electrode active material, wherein M and X are independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al.
2. The mass of the first positive electrode active material is m 1 and The mass of the second positive electrode active material is m 2 and m 1 / (m 1 +m 2 2. The positive electrode active material according to claim 1, wherein the value of (a) is 2% to 55%.
3. b x m 1 / (m 1 +m 2 2. The positive electrode active material according to claim 1, wherein the value of is 0.017 to 0.
457.
4. the first positive electrode active material is a single crystal or pseudo-single crystal material; The particle size D of the first positive electrode active material v The positive electrode active material according to claim 1 , wherein 50 is 5.8 μm or less.
5. When the first positive electrode active material is a single crystal or pseudo-single crystal material, and / or, d is selected from the range of 0.047 to 0.320; and / or The positive electrode active material according to claim 1 , wherein the b is selected from the range of more than 0.314 and less than 0.
97.
6. When the first positive electrode active material is a polycrystalline material, The particle size D of the first positive electrode active material v 50 is 3.0 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 2.90 g / cm 3 The positive electrode active material according to claim 1 .
7. The first positive electrode active material further contains lithium carbonate and / or lithium hydroxide, 4. The positive electrode active material according to claim 1, wherein a mass content of the lithium carbonate is 1.05% or less and / or a mass content of the lithium hydroxide is 1.02% or less, based on a mass of the first positive electrode active material.
8. 4. The cathode active material according to claim 1, wherein in the core, the ratio of y to 1-y is from 1:10 to 10:
1.
9. 4. The cathode active material according to claim 1, wherein in the core, the ratio of z to 1-z is from 1:999 to 1:
9.
10. 4 . The positive electrode active material according to claim 1 , wherein a coating amount of the first coating layer is greater than 0 wt % and not more than 7 wt % based on the weight of the core.
11. 4. The positive electrode active material according to claim 1, wherein a weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:
1.
12. The positive electrode active material according to any one of claims 1 to 3, wherein the crystallinity of the pyrophosphate and the crystallinity of the phosphate are each independently 10% to 100%.
13. 4. The positive electrode active material according to claim 1, wherein a coating amount of the second coating layer is greater than 0% by weight and not more than 6% by weight, based on the weight of the core.
14. 4. The positive electrode active material according to claim 1, wherein A is at least two elements selected from the group consisting of Fe, Ti, V, Ni, Co, and Mg.
15. 4. The positive electrode active material according to claim 1, wherein the second positive electrode active material has a Li / Mn antisite defect concentration of 4% or less.
16. The positive electrode active material according to claim 1 , wherein a lattice change rate of the second positive electrode active material before and after complete release of lithium is 6% or less.
17. 4. The positive electrode active material according to claim 1, wherein the second positive electrode active material has a surface oxygen valence of −1.88 or less.
18. The compaction density of the second positive electrode active material at 3 T is 2.0 g / cm 3 The positive electrode active material according to claim 1 .
19. In the second positive electrode active material, the crystal plane spacing of the pyrophosphate in the first coating layer is 0.293 to 0.326 nm, and the angle of the crystal orientation (111) is 26.41° to 32.57°, and / or The positive electrode active material according to any one of claims 1 to 3, wherein the crystal plane spacing of the phosphate in the first coating layer is 0.345 to 0.358 nm, and the angle of the crystal orientation (111) is 24.25° to 26.45°.
20. A method for producing a positive electrode active material, comprising the steps of: providing a first active cathode material and a second active cathode material; mixing the first positive electrode active material with the second positive electrode active material; The first positive electrode active material is the compound LiNi b Co d Mn e M' f O 2 Including, the second positive electrode active material includes a core, a first coating layer coating the core, and a second coating layer coating the first coating layer, Where: The core is the compound Li 1+x Mn 1-y A y P 1-z R z O 4 Including, The first coating layer is a pyrophosphate M a P 2 O 7 and Phosphate X n P.O. 4 and the second coating layer comprises carbon; Where: The definitions of a, b, d, e, f, x, y, z, n, A, R, M, X and M' are as set out in any one of claims 1 to 3. The method for producing a positive electrode active material, wherein the first positive electrode active material further contains lithium carbonate and / or lithium hydroxide.
21. A positive electrode plate, A positive electrode current collector; a positive electrode film layer disposed on at least one surface of the positive electrode current collector; 4. A positive electrode plate, wherein the positive electrode film layer comprises the positive electrode active material according to claim 1, and a content of the positive electrode active material in the positive electrode film layer is 10 wt % or more based on a total weight of the positive electrode film layer.
22. A secondary battery comprising a positive electrode active material described in any one of claims 1 to 3.
23. A battery module comprising the secondary battery according to claim 22.
24. A battery pack comprising the battery module of claim 23.
25. A power consuming device comprising the battery pack of claim 24.
Citation Information
Patent Citations
Phosphate compound, positive electrode material for secondary battery, and method for producing secondary battery
JP2014056722A
Positive electrode material for lithium ion batteries, method for manufacturing the same and application thereof
JP2016127002A
Manufacturing method of cathode active material composite material for lithium ion secondary battery
JP2020113377A
Secondary battery, battery module, battery pack and electric device
JP2024514739A